Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
(-1, -2)
x=-1
y=-2
Step-by-step explanation:
x+y=2
y=2x
Knowing this information, we can substitute y for 2x+5 in the first equation.
x+2x+5=2
3x+5=2
3x=-3
x=-1
Now, plug x into the second equation.
y=2(-1)
y=-2
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.